Principles for Integration: Learning from Public Interest Design - Jill Sornson Kurtz (Oz, 2013)
As the mementoes of the assembly line approach the past, the last century’s building portfolio epitomizes the industrialized era in which it was produced. Isolating energy systems and siloing disciplines from each other for efficiency’s sake has resulted in a collection of buildings that are anything but efficient.